Unravelling the power relations in high school sexuality education text: who is represented? - Rossouw, Jane (My University, 2021)
A continuous challenge in post-apartheid SA is the construction and teaching of sex and sexuality in school to be aligned with diversity, inclusion and social transformation. The objective of this research was to determine how sex and sexuality content is represented in SA high school textbooks, focusing specifically on the learning areas of Life Orientation and Life Sciences. Although not as extensively examined as Life Orientation regarding sex and sexuality education, Life Sciences was included in this study as it does contain sex education content, specifically that related to reproduction. The purpose of examining the two subjects was to determine how, collectively, these subjects represent sex and sexuality. A critical discourse analysis of the textbooks for both learning areas revealed a common theme of epistemic ignorance- a notion that the text claims diversity, inclusivity and social transformation, yet actively reproduces hegemonic narratives of heteronormativity and christonormativity, and the expectation of students to be contributing members of a heteronormative and christonormative society.
This research report submitted for the fulfilment of the requirements for a Master of Arts in Critical Diversity Studies to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2021